MASCC clinical practice guidelines for the prevention and management of acute radiation dermatitis: part 1) systematic review. (April 2023) - Behroozian, Tara; Goldshtein, Daniel; Ryan Wolf, Julie; van den Hurk, Corina; Finkelstein, Samuel; Lam, Henry; Patel, Partha; Kanee, Lauren; Lee, Shing Fung; Chan, Adrian Wai; Wong, Henry Chun Yip; Caini, Saverio; et al.
Summary: Acute radiation dermatitis (ARD) commonly develops in cancer patients undergoing radiotherapy and is often characterized by erythema, desquamation, and pain. A systematic review was conducted to summarize the current evidence on interventions for the prevention and management of ARD. Databases were searched from 1946 to September 2020 to identify all original studies that evaluated an intervention for the prevention or management of ARD, with an updated search conducted in January 2023. A total of 235 original studies were included in this review, including 149 randomized controlled trials (RCTs). Most interventions could not be recommended due to a low quality of evidence, lack of supporting evidence, or conflicting findings across multiple trials. Photobiomodulation therapy, Mepitel® film, mometasone furoate, betamethasone, olive oil, and oral enzyme mixtures showed promising results across multiple RCTs. Recommendations could not be made solely based on the published evidence due to limited high-quality evidence. As such, Delphi consensus recommendations will be reported in a separate publication.